Rancang Bangun Web Untuk Pengontrolan Arah Putaran Motor Secara Online Dan Realtime - Ibnu Kholib; Irsan Taufik Ali; Rahyul Amri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
WEB this particular internet technology can be used to overcome distance remote control system. In this case theauthor uses an object-oriented programming language is Visual Basic 6. For system expansion, it would be better touse a programming language that supports WEB such as ASP, Java or PHP. So that this system can be developed byutilizing Web-based HTTP.Keywords;Internet, WEB, DC motors